2020
DOI: 10.1177/0973703020948468
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Income Inequality on Happiness Inequality in India: A Recentered Influence Function Regression Estimation and Life Satisfaction Inequality Decomposition

Abstract: It is now an accepted stylised fact that increase in happiness level in any country is not commensurate with growth in income, a puzzle known as Easterlin Paradox. This paper analyses the income-happiness relationship in India and tries to explain the flat happiness response to income change in terms of rising income inequality. Income growth propels inequality and so also inequality in well-being. Empirically the effects of income inequality, absolute income, relative income, rank position and social capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
(91 reference statements)
4
2
0
Order By: Relevance
“…However, for Indians, per capita income negatively influences happiness. This finding supports the result of Lakshmanasamy and Maya (2020), who found that happiness is not increased with the increased income across Indian states. Inequalities in life satisfaction and income, regional differences, increasing aspirations, and status consciousness are the possible causes of reduced happiness in India.…”
Section: Resultssupporting
confidence: 90%
“…However, for Indians, per capita income negatively influences happiness. This finding supports the result of Lakshmanasamy and Maya (2020), who found that happiness is not increased with the increased income across Indian states. Inequalities in life satisfaction and income, regional differences, increasing aspirations, and status consciousness are the possible causes of reduced happiness in India.…”
Section: Resultssupporting
confidence: 90%
“…The empirical result revealed that the growth of income indicates able to reduce such happiness inequality in Germany. That is to say, the more income inequality decrease, the more society's happiness increase (Becchetti, Masaari, & Naticchioni, 2014), this finding was consistent through the research of ( Lakshmanasamy & Maya, 2020). While some empirical studies which produce that there is positive association between income inequality and happiness are (Haller & Hadler, 2006;Helliwel & Huang;ect, Zagorsk, & Piotrowska, 2014), which revealed that income inequality increase such happiness, evidence from China through its effects on rural resident, who are optimistic about their life.…”
Section: Resultssupporting
confidence: 65%
“…Hence, it may show SC individuals' heightened fear of downward mobility as opposed to their higher caste colleagues (Iversen et al, 2016). The combination of these trends makes persons of lower castes more prone to unemployment and downward social mobility, which in turn might lead to worse well-being and life satisfaction outcomes (Bartelink et al, 2020;Lakshmanasamy & Maya, 2020;Sinha, 2018), which is also congruent in the authors' findings.…”
Section: Caste Differencessupporting
confidence: 77%